An Analysis of Homestay Hosts Interest in Learning English at Tamansari Tourism Village - Umi Musleha; Abdul Halim; Sutami Dwi Lestari (Prodi Pendidikan Bahasa Inggris, Universitas PGRI Banyuwangi, 2021)
English is important language to communicate with the foreign guests who stay at the homestay. This research aimed to describe how the Homestay hosts interest in learning English at Tamansari tourism village. The research design was descriptive qualitative. The respondents were 22 homestay hosts in Tamansari tourism village which determined by using purposive sampling. The data were taken by using questionnaire and interview. The data from questionnaire was analyzed by using Likert scale. The data analysis was determined based on theory of interest with four indicators. They are attention, participation, willingness, and feeling need. Analysis questionnaire and interview data showed that homestay hosts in Tamansari tourism village have high interest in learning English and the index percentage was 74%. It consists of attention level 78%, participation level 64%, willingness level 71%, and feeling need level 74%. Therefore the homestay hosts in Tamansari tourism village need English as communication medium with the foreign tourists. On the other case, there were some problems faced by the homestay hosts that are pronunciation, lack of time, lack of partner to learn, fluctuation of foreign tourists visit, and low awareness to learn made them practice English less maximal.